The ancient chinese - Bryan, Jullen; International Film Foundation ([ New York] : International Film Foundation, 2009)
Presents highlights of Chinese history, focusing on major dynasties. Relates eminent achievements of each period to the present and tells of the influence of ancient Chinese tradition on contemporary Chinese life-styles
DVD format
Keywords: China -- Civilization; China -- History; China -- Social life and customs